Perancangan Sistem Absensi Dengan RFID Berbasis IoT Menggunakan NODEMCU ESP8266 Terhadap PT Halal Fresh Indonesia - Daffa, Raihan; Moenir, Ardianto (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
There is a fact that PT. Halal Fresh Indonesia still uses employee attendance records using an attendance book, this can lead to inefficiencies when checking attendance data and also hampering employee performance, due to the long queues to take attendance. This study aims to design a prototype of an automatic attendance system using RFID (Radio Frequency Identification) technology and operated by the Nodemcu ESP8266 microcontroller which is integrated into the web. This tool serves to support the program to improve employee discipline as a first step in improving the company's overall work performance by recording every employee who is late or on time through an attendance tool in addition aims to prevent queues and crowds due to the enactment of PSBB (Pembatasan Sosial Berskala Besar). The results of this research are a prototype web-based attendance system that makes it easier for admins to process attendance data every month for company evaluation materials and also minimizes queues and crowds during employee absences, so that the problem of delays experienced by employees does not have an impact on employee performance.